2015
DOI: 10.1080/00913847.2015.1020248
|View full text |Cite
|
Sign up to set email alerts
|

A review and clinical summary of vitamin D in regard to bone health and athletic performance

Abstract: The large amount of scientific literature regarding vitamin D can be overwhelming and confusing. Some organizations have made specific guidelines and recommendations regarding optimal blood levels of vitamin D. In the sports medicine literature, new information about the effects of vitamin D on performance and bone health abound. Most of these articles seem to raise more questions than they answer. Are athletes at increased risk of vitamin D deficiency? Does vitamin D deficiency affect athletic performance? Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Vitamin D status is also a regulator of intestinal Ca absorption and, in turn, bone mineralisation (125) . In this context, several reviews have concluded that there is a positive outcome for supplementation of Ca plus vitamin D for fracture risk reduction, osteoporosis and/or falls (6,(126)(127)(128) . In contrast, recent metaanalyses have not been consistent with these outcomes, though many variables need to be considered when comparing studies, for example, the parameters analysed, age of the population, if participants live in residential institutions, dose and cut points of vitamin D, ethnicity, period of the intervention, instruments to assess Ca and vitamin D intake and sunlight exposure, and many others (129) .…”
Section: Clinical Studies and Perspectivesmentioning
confidence: 99%
“…Vitamin D status is also a regulator of intestinal Ca absorption and, in turn, bone mineralisation (125) . In this context, several reviews have concluded that there is a positive outcome for supplementation of Ca plus vitamin D for fracture risk reduction, osteoporosis and/or falls (6,(126)(127)(128) . In contrast, recent metaanalyses have not been consistent with these outcomes, though many variables need to be considered when comparing studies, for example, the parameters analysed, age of the population, if participants live in residential institutions, dose and cut points of vitamin D, ethnicity, period of the intervention, instruments to assess Ca and vitamin D intake and sunlight exposure, and many others (129) .…”
Section: Clinical Studies and Perspectivesmentioning
confidence: 99%
“… 1 The incidence of hypovitaminosis D is rising globally, affecting approximately one billion people. 2 Staying indoors for prolonged periods, wearing clothes that cover the skin, and using sunscreen are some of the primary causes of this increasing epidemic, the repercussions of which remain obscure. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D 3 also facilitates bone mineralization and its deficiency contributes to the disturbance in remodeling processes with a simultaneous delay in bone growth [ 16 ]. Inadequate dietary intake of calcium contributes to increased bone turnover due to vitD 3 and PTH [ 17 ].…”
Section: Introductionmentioning
confidence: 99%